Management of mountain forests in the hydrology of a landscape, the Czech Republic - F. Šach; V. Švihla; V. Černohous; P. Kantor (Journal of Forest Science, 2014)
Forests important from a water-management perspective cover 723,000 ha of the Czech Republic (CR), i.e. 27.6% of the forest area. These forests play an important role especially in a mountain landscape. Forests decrease peak flood flows, compensate water discharge and represent a source of high-quality fresh water. The optimum hydrological function is provided by forests that are healthy, ecologically stable, diversified, proper to site, growing on a good forest soil, managed by small-area felling and emulating natural processes. For mountain sites of the CR, the optimum proportion of Norway spruce (+ Silver fir) ranges from 70 to 80% and of European beech from 20 to 30%. Clear-cuts due to air pollution disasters led to replacement of the forest stand by perennial grassland increasing stormflows and decreasing the soil water supply to groundwater resources and the quality of water discharged from the forest. Skidding and hauling operations and an improperly constructed and maintained road network increased the surface runoff from a forest. Intraskeletal erosion occurs on pollution-disaster stone fields and in dying forest stands on stony sites. Reforestation of stone fields is necessary for the preservation of forests on stony and bouldery localities and their services for the cultural landscape situated below. In mountain headwaters, torrent control and forest amelioration are of great importance. These decrease peak flood flows, compensate water discharge and reduce bed-load and sediment transport. Forest amelioration enables the reforestation of waterlogged pollution-disaster areas.